Strategic studies and public policy : the American experience - Gray, Colin S. (Essays for the third century., 2015)
Strategic studies as a field of civilian scholarship has developed along distinctive lines in the United States since World War II. The rapid proliferation and increasing sophistication of weapons technology have required constant revision of strategic theory, while the shifting political climate, both internationally and in the United States, has had an equally powerful impact. One of the field's leading theorists now examines the history and development of American strategic studies, the varied roles assumed by civilian strategists, and their relationship with those charged with developing an.